2005
DOI: 10.1080/00071660500065789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensity of eggshell pigment and illuminated incubation on hatchability of brown eggs

Abstract: The effects of intensity of brown eggshell pigment (light (LBP), medium (MBP) and dark (DBP)) and light intensity during incubation (low and high, 900 to 1380 and 1430 to 2080 lux, respectively) on eggshell characteristics, embryonic growth, hatchability traits, chick hatching weight and hatching time were investigated using eggs from a meat-type breeder (Hybro) flock at 32, 36 and 41 weeks of age in three trials. With eggs of similar weights the intensity of brown pigment was not associated with eggshell weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 12 publications
4
43
3
1
Order By: Relevance
“…The eggshell itself is an important factor in how light effects the embryo as it absorbs most of the light it is exposed to 2005). Huth and Archer (2015) noted that white light is filtered in a manner that the wavelengths of light are shifted to the red hue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eggshell itself is an important factor in how light effects the embryo as it absorbs most of the light it is exposed to 2005). Huth and Archer (2015) noted that white light is filtered in a manner that the wavelengths of light are shifted to the red hue.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in hatch time have been attributed to the eggshell filtering of certain light spectrums (Ghatpande et al, 1995). Furthermore, it has been observed that only some of the light reaches the embryo with an average of 99.8% of the light being absorbed by the shell 2005). Huth and Archer (2015) observed that broiler eggs saw an increase in hatchability when exposed to white lightemitting diode (LED) light, whereas white layer eggs showed no improvement in hatchability over eggs incubated in darkness and concluded that this may be related to how the broiler and layer eggs filter the light differently due to different shell pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of the hatchability of pheasant eggs of different colours, it was reported that fertility, hatchability and hatchability of fertilized eggs were higher in brown eggs than in eggs of other colours (21,22). Shafey et al (34) reported that differences in hatchability and embryonal mortality might be related to differences in pigment density in the eggshell and that eggshell pigmentation could play a key role in shielding the egg's contents from harmful radiation and hence successful embryonic development. Nevertheless, reasons for an association between hatchability and eggshell colour are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Egg weight and eggshell colour are two physical factors that influence hatchability. Their effects on hatchability have been studied for hens (1,31,34,37), wild birds (25,26) and pheasants (4,14,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Shafey et al (2005) reported that high light intensity during incubation reduced the hatchability of light-brown and medium-brown eggs, but not of dark-brown eggsin laying hens. Dark eggs from a same breeder flocks presented better incubation results than light eggs (Erensayın, 1991).…”
Section: Introductionmentioning
confidence: 99%